Current designs of polymer blends in solid dispersions for improving drug bioavailability - Tran, Phuong H.L.; Duan, Wei; Lee, Beom Jin; Tran, Thao T.D. (Current Drug Metabolism, 2018)
Background: Ternary solid dispersions have been demonstrated to be an effective strategy in the improvement of drug absorption and bioavailability. Method: The applications of the combination of hydrophilic polymers with the potential of hydrophobic polymer incorporation at moderate concentrations have been discussed in recent publications. Results: In this paper, the general review of this specific type of solid dispersion will be provided with comprehensive understanding of polymer blends of either hydrophilic or hydrophobic polymers. A detailed description of miscible polymers has been developed in recent studies. In addition to dissolution rate improvement, the role of second polymers in crystal growth inhibition and in maintaining the amorphous state will be mentioned. Conclusion: We also present a summary of characterization techniques commonly used to evaluate solid dispersion and polymer miscibility.
Keywords: Biological Availability; Drug Design; Hydrophobic and Hydrophilic Interactions; Pharmaceutical Preparations; Polymers; Dissolution; Hydrophilic-hydrophobic polymer; Polymer blend; Polymer miscibility; Poorly water-soluble drugs; Ternary solid dispersion